The use of intraoperative fascial traction in W3-incisional hernia repair: A revolution or an emergency exit (two case reports) - Jurij Gorjanc; Christiane Dreschl; Sigrid Trieb; Maria Greiner; Andreas Grün; Pero Zanchi; Manfred Kuschnig; May Cathleen Müller; Alexander Engels; Jörg Tschmelitsch (International Journal of Abdominal Wall and Hernia Surgery, 2023)
In the modern era of tension-free hernia repairs, any tissue tension seems to be counterproductive. It was believed to cause tissue damage, hemorrhage, and chronic pain, and lead to higher early or late recurrence rates. Surprisingly, recently published data on intraoperative fascial traction do not confirm this harmful effect of tissue tension in the cases of sufficiently wide mesh augmentation. On the contrary, the traction was reported to be beneficial in order to approximate large hernia defects and at the same time avoid the wide tissue preparation of component separation (CS) techniques. Below is presented our initial and positive experience regarding this after intraoperative fascial traction was used in two patients, each of them with a large incisional hernia (W3). Without intraoperative traction, the linea alba could not have been approximated in patient 1 without CS, and a large bridging of the linea alba would have been necessary in patient 2. The duration of hospitalization in both patients was short and there were no negative long-term results. It seems that intraoperative fascial traction facilitates the closure of hernia defects. It can serve as a useful adjunct tool in the surgery of large midline incisional hernias (W3) in the future. However, more data are needed to better evaluate this method.